THE POLITICAL ECONOMY OF KNOWLEDGE: Shari`ah and Saudi Scholarship in Indonesia - Jajang Jahroni (State Islamic University (UIN) of Sunan Ampel Surabaya, 2013)
This article investigates how the Saudi regime uses sponsorship to support its educational system in Indonesia. The article focuses its analysis on LIPIA (Lembaga Ilmu Pengetahuan Islam dan Arab, Institute for the Knowledge of Islam and Arab). LIPIA is an Islamic institution consistent using traditional Islamic scholarship especially those of the Hanbalite schools of thought. This is reflected in the entire curriculum the LIPIA has for its students. The writer argues that the relationship between the sponsor, i.e. the Saudi state, and the sponsorship beneficiaries, i.e. students, is patron-client. Nevertheless, it involves a wide range of actors thereby allowing the diversity of knowledge reproduction. Over the last three decades, it has made a big investment on the field of education by building Islamic schools and institutes, distributing scholarship for Indonesian students, and channeling aid for Muslim organizations. It is becoming obvious that Saudi uses education as a political strategy to maintain its influences over Indonesia.